Любимые стихи - Заходер Борис Владимирович (Любимые стихи, 1996)
Экземпляры: ф.5 (1997) / Инвентарный номер: 39788 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: З-38 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-5